Assessment of the developmental and neurotoxicity of the mosquito control larvicide, pyriproxyfen, using embryonic zebrafish. (November 2016) - Truong, Lisa; Gonnerman, Greg; Simonich, Michael T.; Tanguay, Robert L.
Abstract: In 2014, as an attempt to address the Zika health crisis by controlling the mosquito population, Brazil took the unprecedented action of applying a chemical larvicide, pyriproxyfen, to drinking water sources. The World Health Organization has established an acceptable daily intake of pyriproxyfen to be 100 μg per kg of body weight per day, but studies have demonstrated that at elevated doses (>5000 mg/kg), there are adverse effects in mice, rats and dogs. To better understand the potential developmental toxicity of pyriproxyfen, we utilized the embryonic zebrafish. Our results demonstrate that the concentration resulting in 50% of animals presenting adverse morphological effects (EC50), including craniofacial defects, was 5.2 μM for daily renewal exposure, and above this concentration, adverse behavioral effects were also observed in animals that followed a static exposure regimen. Thus, zebrafish data suggest that the developmental toxicity of pyriproxyfen may not be limited to insects. Graphical abstract: Highlights: Rapid 5-day zebrafish assay detected developmental and behavioral effects of pyriproxyfen. 50% adverse effect (EC50) was 5.2 μM for daily renewal exposure. Behavioral effects observed at concentrations higher than 6.4 μM. Abstract : In the zebrafish model, daily renewal of 5.2 μM pyriproxyfen resulted in 50% of the test subjects showing morphological defects and similar pyriproxyfen exposures resulted in adverse behavioral effects.